2012
DOI: 10.3389/fnhum.2012.00144
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive tactile stimulation changes resting-state functional connectivity—implications for treatment of sensorimotor decline

Abstract: Neurological disorders and physiological aging can lead to a decline of perceptual abilities. In contrast to the conventional therapeutic approach that comprises intensive training and practicing, passive repetitive sensory stimulation (RSS) has recently gained increasing attention as an alternative to countervail the sensory decline by improving perceptual abilities without the need of active participation. A particularly effective type of high-frequency RSS, utilizing Hebbian learning principles, improves pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 98 publications
1
53
1
Order By: Relevance
“…In addition, fatigue-terminal AD thresholds were significantly greater in the condition with sensory stimulation than when stimulation was absent (Time × Condition interaction). Despite previous research demonstrating that sensory supplementation has a beneficial effect on sensory function (Freyer, Reinacher, Nolte, Dinse, & Ritter, 2012;Kalisch, Tegenthoff, & Dinse, 2008), our data suggest that stimulation may add the effects of fatigue on the sensory system and lead to a larger decrease in sensory detection capability. Results from other experimental fatigue protocols have found significant increases in sensory thresholds of both fatigued and nonfatigued muscles (Han et al, 2015;Kosek & Lundberg, 2003;Moufflet & Côté, 2015).…”
Section: Discussion Motor and Sensory Adaptations To Fatigue-inducingcontrasting
confidence: 51%
“…In addition, fatigue-terminal AD thresholds were significantly greater in the condition with sensory stimulation than when stimulation was absent (Time × Condition interaction). Despite previous research demonstrating that sensory supplementation has a beneficial effect on sensory function (Freyer, Reinacher, Nolte, Dinse, & Ritter, 2012;Kalisch, Tegenthoff, & Dinse, 2008), our data suggest that stimulation may add the effects of fatigue on the sensory system and lead to a larger decrease in sensory detection capability. Results from other experimental fatigue protocols have found significant increases in sensory thresholds of both fatigued and nonfatigued muscles (Han et al, 2015;Kosek & Lundberg, 2003;Moufflet & Côté, 2015).…”
Section: Discussion Motor and Sensory Adaptations To Fatigue-inducingcontrasting
confidence: 51%
“…Few studies have demonstrated improvement of limb function (as scored by validated outcome measures) in patients treated to reduce excitability in contralesional M1, both in the sub-acute and in the chronic phase after stroke [48].The ability to recover motor functions after stroke is strongly influenced by the integrity of high-speed fibres connecting M1 to the spinal cord [14]. Since brain plasticity is virtually maintained regardless of age, changes in environmental conditions may impact the reorganisation of the cerebral cortex [49]. These findings indicate that there is potential for functional plasticity in the cerebral cortex of adults and suggest that rehabilitation programmes may influence this process.…”
Section: Neuroplasticity and Brain Repair After Strokementioning
confidence: 99%
“…In addition to topographical changes, rTS influences connectivity of the sensory cortex, through interactions of sensory, motor and association cortices (Freyer et al, 2012). Evidence for this stems from EEG resting state measurements, which supported an increased connectivity of these areas after stimulation (Freyer et al, 2012).In order to estimate the connectivity, EEG coherence was measured during the resting state. This measure measures in how far the neuronal dynamics in different regions correlate.…”
Section: Cortical Excitabilitymentioning
confidence: 99%
“…Here, burst stimuli, with inter-burst intervals of about 5 seconds were used (Freyer, Reinacher, Nolte, Dinse, & Ritter, 2012;Freyer, Becker, Dinse, & Ritter, 2013;Kalisch et al, 2007;Tossi, Stude, Schwenkreis, Tegenthoff, & Dinse, 2013).…”
Section: Different Stimulation Protocolsmentioning
confidence: 99%
See 1 more Smart Citation